2001
DOI: 10.1248/jhs.47.36
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in the Metabolic Activation of Chlorinated Ethylenes by Cytochromes P450 in Primary Rat Hepatocytes.

Abstract: The manifestation of toxicity by certain environmental compounds requires enzymatic activation. It is well known that chlorinated ethylenes (CEs) are metabolized by intracellular enzymes represented by cytochromes P450 (CYPs) to the urinary secreted forms via epoxide intermediates, which are responsible for their toxicities by forming complexes with intracellular components including CYPs. In order to study the roles of CYPs in the metabolic activation of tetrachloroethylene (PCE), trichloroethylene (TCE) or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In this study, however, CEs were found to suppress the expression of CYP forms in vivo. CEs are metabolically activated by CYP forms to show their toxicities, 14) to which various host defense systems were mobilized to reverse the toxicities of CEs. The expressions of CYP forms are reportedly down-regulated by interleukins, 15) insulin, 16) active oxygen species, 5) glucocorticoide 17) etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, CEs were found to suppress the expression of CYP forms in vivo. CEs are metabolically activated by CYP forms to show their toxicities, 14) to which various host defense systems were mobilized to reverse the toxicities of CEs. The expressions of CYP forms are reportedly down-regulated by interleukins, 15) insulin, 16) active oxygen species, 5) glucocorticoide 17) etc.…”
Section: Discussionmentioning
confidence: 99%
“…CYP forms of families 1 through 4 are enzymes with a wide range of substrates which partially overlap, and the forms mainly responsible for the metabolic activation of individual CEs were divergent. 10) When CEs were administered to the rats intraperitoneally, suppression of hepatic EROD activity was observed. 11) In this paper, CEs were found to induce the expression of CYP1A in rat hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…dichloroethylene (1,1-DCE), known as environmental pollutants, are metabolized by CYPs to form epoxide intermediates, which are responsible for their toxicity and carcinogenicity. 9,10) In our previous study, however, CEs were found to suppress hepatic ethoxyresorufin O-deethylase (EROD) activity (CYP1A) in rats. 11) In the present study, the effects of CEs on the expression of CYP1A were examined in vitro using human hepatoma HepG2 cells and rat primary cultured hepatocytes in order to elucidate whether the suppressive effects in vivo are conferred directly or not.…”
Section: Introductionmentioning
confidence: 94%
“…9) We reported that CYP1A, 2B, and 2E1 were mainly responsible for the metabolic activation of tetrachloroethylene (PCE), trichloroethylene (TCE), and 1,1-DCE, respectively. 10) On the contrary, chlorinated ethylenes (CEs) have been studied extensively for their effects on the expression of CYP1A, 2B, and 2E1 in animal models. 5,[11][12] Although CYP2C is reportedly one of the major P450 forms by which CEs are metabolized, 13) the effects of CEs on the expression of CYP2C have not been studied extensively.…”
Section: )mentioning
confidence: 99%